A survival analysis of GBM patients in the West of Scotland pre- and post-introduction of the Stupp regime. (June 2014) - Teo, Mario; Martin, Sean; Owusu-Agyemang, Kevin; Nowicki, Stefan; Clark, Brian; Mackinnon, Mairi; Stewart, Willie; Paul, James; St George, Jerome
Abstract Objective. It is now accepted that the concomitant administration of temozolomide with radiotherapy (Stupp regime), in the treatment of patients with newly diagnosed glioblastoma multiforme (GBM), significantly improves survival and this practice has been adopted locally since 2004. However, survival outcomes in cancer can vary in different population groups, and outcomes can be affected by a number of local factors including socioeconomic status. In the West of Scotland, we have one of the worse socioeconomic status and overall health record for a western European country. With the ongoing reorganisation and rationalisation in the National Health Service, the addition of prolonged courses of chemotherapy to patients' management significantly adds to the financial burden of a cash stripped NHS. A survival analysis in patients with GBM was therefore performed, comparing outcomes of pre- and post-introduction of the Stupp regime, to justify the current practice. Materials and methods. Prospectively collected clinical data were analysed in 105 consecutive patients receiving concurrent chemoradiotherapy (Stupp regime) following surgical treatment of GBM between December 2004 and February 2009. This was compared to those of 106 consecutive GBM patients who had radical radiotherapy (pre-Stupp regime) post-surgery between January 2001 and February 2006. Results. The median overall survival for the post-Stupp cohort was 15.3 months (range, 2.83–50.5 months), with 1-year and 2-year overall survival rates of 65.7% and 19%, respectively. This was in comparison with the median overall pre-Stupp survival of 10.7 months, with 1-year and 2-year survival rates of 42.6% and 12%, respectively (log-rank test, p < 0.001). Multivariate Cox regression analysis showed that independent prognostic factors for better survival were younger age, greater extent of surgical resection and a post-operative chemoradiotherapy regime. Conclusion. Significant survival benefit has been achieved, following the introduction of the Stupp regime, in GBM patients in the West of Scotland.